Stressors in the marine environment : physiological and ecological responses ; societal implications - Solan, Martin; Whiteley, Nia M. (Oxford University Press, 2016)
This edited work summarises the latest advances in the physiological and ecological responses of marine species to a wide range of potential stressors resulting from current anthropogenic activity. It provides a perspective on future outcomes for some of the most pressing environmental issues facing society today.